Behavior Management: Traditional and Expanded Approaches - Haynes, Norris M. (University Press of America, 2013)
This book serves as a reference guide on the implementation of basic and more advanced behavior management strategies. It covers the principles and application of basic learning theories as well as those that integrate cognitions and emotions in treatment frameworks. It takes the reader through the essential steps in developing behavior management plans, including conducting functional behavior analyses and curriculum-based assessments. The contributors describe and share examples of various behavioral intervention techniques that address behavioral challenges in a variety of settings. These methods include more traditional approaches, such as classical and instrumental learning strategies and cognitive behavior management techniques. They also discuss less traditional and alternative approaches, including social and emotional learning, character development, and yoga. The book is appropriate for professionals in various specialty areas, including classroom teachers, college professors, and undergraduate and graduate students majoring in general education, special education, school psychology, psychology, educational leadership, school counseling, and social work. It is also appropriate for professionals who work with children on the autism spectrum and for board certified behavioral analysts.
Keywords: Education; Human behavior; Teaching; Individualized instruction; Problem children; dept.csp

Clinical Interviewing and Counseling Skill Development: Global Perspectives on Client Change - Nwachuku, Uchenna T. (Linus Publications, 2013)
Keywords: Interviewing in mental health; Interviewing in psychiatry; dept.csp; faculty_collection

Assessment - Foss-Kelly, L. (Values and Ethics in Counseling: Real-Life Ethical Decision Mak., 2013)
Journal Abbreviation: Values and Ethics in Counseling: Real-Life Ethical Decision Mak.
Keywords: dept.csp

Evaluation, assessment, and interpretation: Assessment - Foss-Kelly, L. (Values and Ethics in Counseling: Real-Life Ethical Decision Mak., 2013)
Journal Abbreviation: Values and Ethics in Counseling: Real-Life Ethical Decision Mak.
Keywords: dept.csp

The added value of the school of the 21st century when combined with a statewide preschool program. - Ginicola, Misty; Finn-Stevenson, Matia; Zigler, Edward (The American journal of orthopsychiatry, 2013)
Although schools have begun to employ multiple programs to reach educational goals, little attention has been paid to the efficacy of combining separate programs. The present study investigates the combination of a school reform model, the School of the 21st Century (21C), and the Arkansas Better Chance (ABC) program, where preschools apply for state funds to provide high quality services to children at risk. To determine if 21C adds anything to the ABC program, the present study compared results from a developmental assessment. The authors compared school-based preschools that had both ABC and 21C services to those programs that offered only ABC services. Results indicated that, at baseline, children within the 21C/ABC programs scored the same or poorer than their ABC-only counterparts. However, at the end of the year, participants at 21C/ABC preschools were significantly ahead of ABC-only programs on all developmental indicators. There were also differences favorable to 21C/ABC preschools between the programs' quality ratings as measured by the Early Childhood Environmental Rating Scale. Copyright © 2013 American Orthopsychiatric Association.
1 citations (Crossref) [2023-10-31] Place: United States Ginicola, Misty. Southern Connecticut State University, New Haven, CT 06511, USA. ginicolam2@southernct.edu
Keywords: *Early Intervention; Educational; *Schools; Arkansas; Arkansas Better Chance program; Child care; Child; Preschool; Early Intervention (Education); Educational Status; Family support; Female; Humans; Male; Poverty; Preschool children; School children; School readiness; Schools; The School of the 21st Century; article; child; dept.csp; education program; female; history; human; male; preschool child; rating scale; school